Omics-driven insights into plant growth-promoting microorganisms for sustainable agriculture - Abhishek Sahoo; Garima Yadav; Tushar Mehta; Mukesh Meena; Prashant Swapnil (Discover Sustainability)
Abstract Plant growth-promoting microorganisms (PGPMs) are pivotal to advancing sustainable agriculture, offering eco-friendly solutions for nutrient acquisition, stress tolerance, and disease suppression. Integrating multi-omics approaches, genomics, transcriptomics, proteomics, and metabolomics has substantially deepened our understanding of plant–microbe interactions at molecular and system levels. Genomic studies have identified key PGPM traits such as nitrogen fixation, siderophore biosynthesis, and stress-responsive gene clusters. At the same time, transcriptomic profiling has illuminated plant immune priming and hormonal modulation under microbial influence. Proteomics analysis have revealed protein networks underpinning microbial colonization, stress adaptation, and metabolite exchange, with specific markers such as ACC deaminase and antioxidant enzymes linked to growth promotion. Metabolomics further elucidates biochemical pathways shaped by PGPMs, including increased levels of flavonoids, osmoprotectants, and signalling molecules in host plants. The application of omics-guided microbial consortia shows enhanced efficacy compared to single-strain inoculants, promoting greater biomass, yield, and stress resilience. Case studies highlight the successful deployment of PGPMs in ameliorating salinity and drought stress, enhancing phytoremediation, and improving nutrient uptake in diverse crops. Despite these advances, challenges persist, including limited omics resolution in complex soil environments, a lack of standardised data integration pipelines, and ecological variability affecting microbial persistence. Emerging technologies like CRISPR-based genome editing and AI-driven consortia design promise to overcome these barriers by tailoring microbial interventions to crop-specific and environmental contexts. This comprehensive review underscores the transformative potential of multi-omics in PGPM research while emphasizing the need for interdisciplinary collaboration to translate molecular insights into field-level agricultural innovations.